NSW parliament's oversight of human rights in the first year of the COVID-19 pandemic. (March 2022) - Cho, Joseph
New South Wales (NSW) relies on a robust application of the Westminster system of government for its human rights protection. In 2020, the system was subjected to a major stress test via the COVID-19 pandemic, with new public conditions imposed on previously unregulated individual freedoms. The author examines the extent to which human rights featured in NSW parliament's oversight of the 2020 pandemic response and finds it inadequate. The author concludes that the case study demonstrates a need for the state's human rights protection model to be reconsidered.